2017
DOI: 10.4103/0259-1162.194589
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin in monitored anesthesia care for ear-nose-throat surgery

Abstract: Aim:The aim of this study was to determine intraoperative sedative and perioperative analgesic requirement and associated side effects of pregabalin (150 mg) for monitored anesthesia care during ear-nose-throat (ENT) surgeries.Materials and Methods:The study design was randomized and single-blinded; fifty patients undergoing elective ambulatory ENT surgeries under monitored anesthesia care were randomly allocated to receive either placebo (Group P) or pregabalin (Group PG) 150 mg, orally 1 h before surgery. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In another study, it was shown that a single dose of pregabalin 150 mg reduced the requirement for intraoperative sedation and postoperative analgesic consumption. [26]. These studies were related to premedication for surgery, but we couldn't find any studies for interventional bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was shown that a single dose of pregabalin 150 mg reduced the requirement for intraoperative sedation and postoperative analgesic consumption. [26]. These studies were related to premedication for surgery, but we couldn't find any studies for interventional bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%